The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1678-457x.19317
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activities of Radix Isatidis polysaccharide against type II herpes simplex virus in vitro

Abstract: This study investigated the antiviral activities of Radix Isatidis polysaccharide (ROP) against type OO herpes simplex virus (HSV-2) in vitro. ROP was prepared from the Radix Isatidis root. The toxicity of ROP on Vero cells was detected. The direct killing effect of ROP on HSV-2, inhibitory effect of ROP on HSV-2 replication and inhibitory effect of ROP on HSV-2 adsorption were determined. Results showed that, ROP in concentration range of 25-800 mg/L had no toxic effect on Vero cells. ROP with different conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The polysaccharide compounds contained in I. radix also have anti-influenza virus activity, as demonstrated by in vitro investigations. It has been reported that a polysaccharide isolated from I. radix inhibited the attachment of the influenza virus to the red blood cells, which promoted the generation of anti-influenza viral IgG antibodies [88]. In a study carried out by Li et al [87], I. radix polysaccharides showed potent anti-influenza A virus activity against human seasonal influenza viruses (H1N1 and H3N2) and avian influenza viruses (H6N2 and H9N2).…”
Section: Antimicrobial and Antiviral Activitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The polysaccharide compounds contained in I. radix also have anti-influenza virus activity, as demonstrated by in vitro investigations. It has been reported that a polysaccharide isolated from I. radix inhibited the attachment of the influenza virus to the red blood cells, which promoted the generation of anti-influenza viral IgG antibodies [88]. In a study carried out by Li et al [87], I. radix polysaccharides showed potent anti-influenza A virus activity against human seasonal influenza viruses (H1N1 and H3N2) and avian influenza viruses (H6N2 and H9N2).…”
Section: Antimicrobial and Antiviral Activitiesmentioning
confidence: 97%
“…The in vitro antiviral efficacy of the I. radix polysaccharide against type II herpes simplex virus (HSV-2) has been recently demonstrated [88]. Using the 3-(4,5-dimethylthiazole-2-yl)-2,5diphenyltetrazolium bromide (MTT) assay, this effect was shown to occur mainly by inhibiting the viral duplication and adsorption.…”
Section: Antimicrobial and Antiviral Activitiesmentioning
confidence: 99%
“…It has the effects of clearing heat, detoxifying, and cooling blood, which can be used for wind-heat cold, epidemic encephalitis, mumps, and hepatitis [2,3]. Modern pharmacological research has confirmed that polysaccharides present in R. isatidis and F. isatidis show antibacterial, antiviral, and immuneenhancing biological activities [4][5][6], which are consistent with the efficacy of CBG. As a result, it is more scientific and reasonable to use polysaccharides analysis as an indicator to evaluate and control the quality of CBG.…”
Section: Introductionmentioning
confidence: 85%
“…It is likely that realgar interacts with bacterial proteins and enzyme proteins, hindering the exchange of substances between bacteria and their environment, thereby exerting bactericidal effects. [19,20] Realgar has also been shown to enhance the defense of Caenorhabditis elegans against Enterococcus faecalis by eliciting immune responses and inducing protective reactions. [21] However, the specific antibacterial and antiviral mechanisms of realgar require further exploration.…”
Section: Modern Pharmacological Research On Realgarmentioning
confidence: 99%